Family stages of adjustment: caregivers' experiences of severe head injury - Burrows, Stephanie (My University, 1997)
Primary caregivers of 8 patients who had sufferd severe closed head injury were assessed [Abbreviated Abstract. Open document to view full version]
Masters by coursework and dissertation in the field of psychology 31 January 1997